PREPARING STUDENTS FOR INNOVATION IN THE LEARNING PROCESS - Parmankulov Farkhad Nurali o'g'li (Bright Mind Publishing, 2025)
The article substantiates the relevance of preparing students for innovative engineering activities through the teaching of an integrated course. It clarifies the concept of innovative engineering activity as a purposeful process that includes the analysis of the current technological level, the synthesis of new technical solutions, the development and creation of new equipment and technologies brought to the level of marketable products. These products are represented by both intangible innovative outcomes-such as intellectual property protection documents, scientific-technical and technological documentation-and tangible ones in the form of goods, works, or services that generate economic, social, or other types of impact, thereby ensuring their competitiveness. A model of a methodological system for preparing students of technical universities for innovative engineering activity within the learning process is developed. This model encompasses objectives, content, methods, forms, and tools of instruction, taking into account interdisciplinary integration and a competency-based approach.
Keywords: Innovation, integration, competence, intellectual activity, innovators (pioneers), innovators (implementers of innovations), infrastructure, motivation.